Investigation of the flexural capacity of glue-laminated Bambusa spinosa Roxb. beams using an experimental procedure and finite element analysis - Sanjie Dutt A. Kumar; Franklyn F. Manggapis; Joe Robert Paul G. Lucena; Aaron Paul I. Carabbacan (Advances in Bamboo Science, 2025)
We examined the flexural capacity of glue-laminated bamboo (GLB) beams made from Bambusa spinosa through experimental four-point bending tests and Finite Element Analysis (FEA) to evaluate mechanical performance, validate numerical models and develop moment capacity equations. We demonstrate that Bambusa spinosa meets structural requirements for engineered bamboo, with GLB100 and GLB125 achieving flexural strengths of 146.78 MPa and 130.66 MPa, respectively. An adhesive shear bond strength of 15.45 MPa ensured durability and structural integrity, while FEA predictions closely aligned with experimental results, confirming the accuracy of numerical modeling in structural analysis. This reinforces the viability of GLB beams as a sustainable alternative to traditional materials, contributing to reducing environmental impact in construction. Economic feasibility, building code limitations and standardization challenges are hindering widespread adoption, necessitating further research on optimizing lamination techniques, adhesive selection, and long-term durability under diverse environmental conditions. This will enhance the applicability of GLB beams in real-world structural designs. Our findings support the advancement of engineering standards for GLB beams, and promoting Bambusa spinosa as a high-strength, eco-friendly solution for sustainable construction.